Cemented carbide, process for preparing the cemented carbide, use of the cemented carbide for the manufacture of tools and parts obtained by forming the cemented carbide
A nanoscale cemented carbide with a cubic metal carbide phase and controlled composition addresses the trade-off between hardness and toughness, offering enhanced mechanical properties for tools and wear parts.
Patent Information
- Application Number
- JP2021518593
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2018-10-12
- Filing Date
- 2019-09-20
- Publication Date
- 2025-01-14
- Estimated Expiration
- 2039-09-20
AI Technical Summary
Conventional cemented carbides face a trade-off between high hardness and fracture toughness, with increasing hardness leading to decreased toughness and brittleness.
A nanoscale or ultra-fine cemented carbide comprising tungsten carbide with a cubic metal carbide phase, such as tantalum carbide, homogeneously distributed with a specific grain size and proportion, combined with a controlled binder metal content, to enhance both hardness and fracture toughness.
The cemented carbide achieves a balanced combination of high hardness and fracture toughness, with improved thermal conductivity, suitable for demanding applications like cutting tools and wear parts.
Smart Images

Figure 0007612572000005 
Figure 0007612572000001 
Figure 0007612572000002
Abstract
Description
[Technical field]
[0001] The present invention relates to a nanoscale or ultrafine hardmetal comprising tungsten carbide, an additional metal carbide phase present in a cubic crystal structure, and a binder metal phase, a process for its manufacture, and its use for the manufacture of tools and wear parts. Furthermore, the present invention relates to parts made from the described hardmetal. [Background technology]
[0002] Cemented carbide is a metal matrix composite material in which a hard material existing as small particles is solidified with a metal matrix. Cemented carbide is widely used in applications requiring high wear resistance, hardness, and high strength. For this reason, cemented carbide is used, for example, as a cutting material for tools (rotary tools, drills, milling tools, etc.) and as a wear-resistant matrix for forming tools and punching tools, for example. However, conventional cemented carbide has a drawback of very low fracture toughness, and its application range is greatly limited. Conventionally, it was possible to improve fracture toughness by increasing the content of binder metal, but this results in a decrease in hardness. Ideally, a tool made of cemented carbide should have high hardness and high fracture toughness at the same time.
[0003] No. 5,593,474 describes a sintered composite body comprising a plurality of regions of a first metal carbide and a plurality of regions of a second metal carbide, the first metal carbide having a larger grain size than the second metal carbide.
[0004] DE 10 2004 051 288 aims to provide a polycrystalline hard material powder which has improved hardness whilst maintaining toughness. This aim is achieved by a polycrystalline hard material powder consisting of polycrystalline hard material particles which consist of crystals of carbides, nitrides and / or carbonitrides of transition metals from groups 4, 5 and 6 of the periodic table (titanium, vanadium and chromium).
[0005] WO 2017 / 186468 relates to a hardmetal comprising a phase of hard material particles and a phase of heterogeneously dispersed binder metal, said hard material particles having an average particle size in the range of 1 nm to 1000 nm, said heterogeneously dispersed binder metal being present in the hardmetal in the form of binder islands with an average size of 0.1 μm to 10 μm and an average distance between adjacent binder islands of 1 μm to 7 μm.
[0006] EP 1 526 189 describes a hard metal comprising a binder phase based on WC, Co, Ni or Fe, and a gamma phase, the gamma phase having an average grain size of less than 1 μm, which is prepared by presynthesizing mixed carbides in the form (Me,W)C.
[0007] CN 103540823 describes a cemented carbide composition comprising 40-50 wt% WC, 5-10 wt% vanadium carbide, 3-8 wt% chromium carbide, 5-9 wt% titanium carbide, 6-1 wt% tantalum carbide, 2-5 wt% niobium carbide, and 12-18 wt% cobalt, the grain size of the WC being in the range of 0.1-0.8 μm.
[0008] EP 1,557 230 relates to a hard alloy body containing 10-12% by weight of cobalt, less than 3% by weight of tantalum carbide, 1-5.5% by weight of niobium carbide, 3-5% by weight of titanium carbide, the remainder being WC, said WC having a grain size of 0.4-1.5 μm, in particular 0.8-1.5 μm.
[0009] US 4,698,266 discloses a cutting tool comprising up to 70% by weight of WC and 5-10% by weight of a cobalt binder phase, the remainder of the composition being formed by a metal carbide selected from the group consisting of TiC, TaC, NbC, HfC and mixtures thereof, the average grain size of said WC being 0.9-1.3 μm. Summary of the Invention [Problem to be solved by the invention]
[0010] Even though some solutions have already been presented in the prior art, there is still no commercial solution for cemented carbide that combines high hardness / wear resistance with high fracture toughness.
[0011] It is therefore an object of the present invention to provide a hard-metal having an improved combination of hardness and fracture toughness, preferably one which is accessible in a simple manner. [Means for solving the problem]
[0012] Surprisingly, it has been found that this object is achieved by providing a nanoscale or ultrafine hardmetal based on tungsten carbide which further comprises a metal carbide phase having a cubic crystal structure at room temperature. [Brief description of the drawings]
[0013] [Figure 1] 1 is a scanning electron microscope photograph of a cemented carbide according to the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0014] The present invention therefore first relates to a hard metal comprising: a) a tungsten carbide phase having an average grain size of 0.05 to 0.5 μm; b) additional metal carbide phases; c) a binder metal phase; 1. A cemented carbide, wherein the additional metal carbide phase is present in a cubic crystal structure at room temperature, the proportion of the additional metal carbide phase in the cemented carbide is at least 4% by volume, based on the total volume of the cemented carbide, and the average grain size is determined by the linear intercept method according to ISO 4499-2.
[0015] Conversion of volume percent to weight percent or weight percent to volume percent is done according to the following formula:
number
number
[0016] The hard metal according to the invention is a nanoscale or ultrafine hard metal, the classification of which complies with ISO 4499-2.
[0017] Within the scope of the present invention, "hard metal" denotes a sintered composite material. Said additional metal carbide phases, which are present in a cubic crystal structure at room temperature, i.e. within the scope of the present invention at 25° C., are hereinafter interchangeably referred to as "cubic metal carbides".
[0018] The cemented carbide according to the invention has high hardness and high fracture toughness. The problem that occurs with conventional cemented carbides, that is, when the hardness of the cemented carbide increases, the fracture toughness decreases, i.e., the material becomes brittle and easily breaks, is not observed in the case of the cemented carbide according to the invention. Without being bound to a particular theory, it is believed that the positive properties of the cemented carbide according to the invention are due in particular to the combination of the small grain size of the tungsten carbide and the presence of a cubic metal carbide phase. Thus, the tungsten carbide used in the cemented carbide according to the invention has an average grain size, measured according to the linear intercept method according to ISO 4499-2, of 0.05 to 0.5 μm, preferably 0.05 to 0.23 μm, more preferably 0.05 to 0.09 μm.
[0019] In a further preferred embodiment, the metal carbide phase, which has a cubic crystal structure at room temperature, is selected from the group consisting of titanium carbide, tantalum carbide, niobium carbide, hafnium carbide, zirconium carbide, mixtures thereof, and mixed carbides of these compounds.
[0020] Preferably, the metal carbide phase used in the cemented carbide according to the invention has an average grain size measured according to the linear intercept method according to ISO 4499-2 of 0.3 to 4.0 μm, preferably 0.5 to 1.5 μm.
[0021] Surprisingly, it has been found that a particularly advantageous relationship between hardness and fracture toughness is obtained if the metal carbide phases present in the cemented carbide according to the invention are uniformly distributed. Preferred embodiments are therefore provided in which the metal carbide phases contained in the cemented carbide are distributed in a regularly repeated manner with an average spacing of 0.5 to 10 μm, preferably 1 to 3 μm. Said average spacing can be determined by linear analysis (linear intercept method) of electron micrographs and refers to the spacing from the center of the grain to the center of the grain. Without being bound to a particular theory, the particularly uniform distribution of the metal carbide phases in the cemented carbide according to the invention is due in particular to the use of tungsten carbide powders having the above-mentioned particle sizes.
[0022] It has been found to be advantageous to use powders with specific grain sizes as starting materials for tungsten carbide and cubic metal carbides. Within the scope of the present invention, "starting material" means unsintered powders. Thus, in a preferred embodiment, the starting material has an average grain size d BET A tungsten carbide powder having an average particle diameter d of 0.05 to 0.30 μm, preferably 0.05 to 0.25 μm, more preferably 0.05 to 0.2 μm is used as the starting material. BET is calculated from the specific surface area of the starting material measured according to BET (BET surface area) using the formula d BET The specific surface area is calculated according to the BET method in accordance with DIN ISO 9277. The density corresponds to the physical density of the pure solid and can be taken from the literature; the density of tungsten carbide is usually 15.7 g / cm. 3 It is said that.
[0023] Cubic metal carbide starting materials are classified into d BET Average particle diameter d calculated using the formula = 6 / (BET specific surface area * density) BET The powder is preferably a cubic metal carbide powder having a particle size of 0.3 to 5 μm, more preferably 0.4 to 1 μm. The density is the physical density of each cubic carbide. The value can be cited from the literature.
[0024] In a preferred embodiment, the binder metal is a compound selected from the group consisting of cobalt, iron, nickel, and mixtures thereof. More preferably, the binder metal is cobalt. In a further preferred embodiment, the binder metal is a mixture of iron, cobalt, and nickel, the proportion of each metal in the mixture being 1% by weight or more.
[0025] Surprisingly, it has been found that the addition of cubic metal carbides alone as described above has no effect on grain growth during the manufacturing process, so that a grain growth inhibitor may be optionally added to inhibit grain growth during the manufacturing process of the cemented carbide according to the invention. Therefore, preferred embodiments are those in which the cemented carbide further comprises a grain growth inhibitor, preferably one selected from the group consisting of vanadium carbide, chromium carbide, mixtures thereof, and mixed carbides of these compounds. The proportion of grain growth inhibitor in the cemented carbide is preferably 0.05-6% by volume, based on the total volume of the cemented carbide.
[0026] Within the scope of the present invention, it has been found to be advantageous if the proportion of tungsten carbide in the cemented carbide according to the invention does not exceed a proportion of 95% by volume. Therefore, preferred embodiments are such that the proportion of tungsten carbide in the cemented carbide according to the invention is 40-90% by volume, based on the total volume of the cemented carbide. This allows the cemented carbide to have sufficient hardness and fracture toughness.
[0027] Furthermore, it has been found to be advantageous to limit the proportion of binder metal in the cemented carbide.Accordingly, preferred embodiments are such that the proportion of binder metal in the cemented carbide according to the invention is up to 40% by volume, preferably 10-32% by volume, respectively, based on the total volume of the cemented carbide.
[0028] Surprisingly, it has been found that a volume fraction of the additional metal carbide phase in the cemented carbide according to the invention of at least 4 wt.-% makes it possible to increase the hardness of the cemented carbide while maintaining its fracture toughness. Preferred are therefore embodiments in which the proportion of the additional metal carbide phase is between 4 and 30 vol.-%, preferably between 10 and 20 vol.-% or between 25 and 37 vol.-%, respectively based on the total volume of the cemented carbide.
[0029] In a particularly preferred embodiment, the cemented carbide according to the invention has the following composition: i) 40 to 90 volume percent of a tungsten carbide phase; ii) 10 to 32 volume percent of a binder metal phase; and Remainder: additional metal carbide phase. wherein the proportion of additional metal carbide phases is at least 4 vol.-%, based on the total volume of the cemented carbide, said vol.-% adding up to 100 vol.-%, each based on the total volume of the cemented carbide, optionally taking into account further components such as grain growth inhibitors.
[0030] Conventional cemented carbides have the drawback that, although the hardness can be improved by reducing the binder metal content, the fracture toughness is reduced. At the same time, an undesirable increase in thermal conductivity may occur. Surprisingly, it has been found that the cemented carbide according to the invention has an advantageous thermal conductivity. In a preferred embodiment, the cemented carbide according to the invention has a thermal conductivity of less than 50 W / m*K, preferably less than 40 W / m*K, measured by the laser flash method at 40° C.
[0031] In addition to advantageous thermal conductivity, the cemented carbide according to the invention is further characterized by an improved fracture toughness. Thus, the cemented carbide according to the invention has a fracture toughness of 8.0 MPa*m, measured by Vickers hardness indentation according to the Palmquist method as described by Shetty et al., Journal of Materials Science 20 (1985), pp. 1873-1882. 1 / 2 The above embodiments are preferred.
[0032] The invention further relates to a process for producing a hard metal according to the invention, comprising: i) providing a powder mix comprising: a) an average particle size d of 0.05 to 0.3 μm, preferably 0.05 to 0.25 μm, and more preferably 0.05 to 0.2 μm; BET Tungsten carbide powder having b) It exists in a cubic crystal structure at room temperature (25°C) and has an average particle size of d BET an additional metal carbide powder having a particle size of 0.3 to 5 μm; and c) a binder metal powder, and ii) forming the mixture and sintering.
[0033] Average particle diameter d BET As mentioned above, d is calculated by converting it into the BET specific surface area. BET It can be calculated using the formula: =6 / (BET specific surface area * density).
[0034] The proportion of said additional cubic metal carbide powder in the powder mixture is selected such that the resulting hardmetal has a proportion of at least 4 volume % of cubic metal carbide phase, based on the total volume of the hardmetal.
[0035] The binder metal powder used is preferably as described above.
[0036] In a preferred embodiment, the shaping and sintering of the mixture provides a hardmetal body, which may be, for example, a part.
[0037] In a preferred embodiment, sintering within the scope of the process according to the invention is carried out at temperatures between 1150 and 1550° C. In this way, the cemented carbide according to the invention is accessible by an industrially easily implementable process.
[0038] Within the scope of the present invention, it has surprisingly been found that in order to produce the cemented carbide according to the invention, it is not necessary to use pre-synthesized mixed carbides in the form of (Me,W)C as described in the prior art. Rather, the cemented carbide according to the invention can be produced from pure metal carbides or mixtures thereof.
[0039] The hard metal according to the invention is particularly suitable for use in applications requiring high hardness and at the same time good fracture toughness. The invention therefore further relates to the use of the hard metal according to the invention for the manufacture of tools, preferably tools with shaped and unshaped cutting edges and for machining all kinds of materials.
[0040] The invention further relates to a part obtained by forming the cemented carbide according to the invention, preferably the part is selected from the group consisting of drills, solid carbide cutters, indexable inserts, saw teeth, forming dies, sealing rings, extrusion punches, press dies and wear parts.
[0041] The present invention will be further illustrated by the following examples, which should not be construed as limiting the scope of the invention in any way. EXAMPLES
[0042] Example 1 As the starting powder, BET WC powder with a value of 90 nm, d BET Cobalt metal powder with a value of 205 nm, d BET TiC powder with a value of 610 nm, d BET TaC powder with a value of 370 nm, d BET Cr3C2 powder with a value of 430 nm, d BETVC powder with a value of 350 nm was used. 200 g of a mixture of 62.7 vol.% (77 wt.%) WC, 15.9 vol.% (11 wt.%) Co, 12.9 vol.% (5 wt.%) TiC, 4.4 vol.% (5 wt.%) TaC, 1.9 vol.% (1 wt.%) Cr3C2, and 2.2 vol.% (1 wt.%) VC was ground in n-heptane in a ball mill for 48 h. The resulting dispersion of cemented carbide was dried and uniaxially pressed at a pressure of 300 MPa to obtain rectangular specimens whose green density was more than 50% of the density expected for the solid (theoretical density). The specimens were compressed under vacuum at a temperature of 1450 °C with a holding time of 30 min to more than 95% of the theoretical density, followed by a final compression at the same temperature under argon atmosphere (Sinter-HIP technique). The specimens proved to be fully dense under an optical microscope. The porosity according to ISO 4505 corresponds to A02, B00, C00. The Vickers hardness is 1770HV10, and the fracture toughness (K 1C ) was calculated by measuring the crack length and using Shetty's formula (Shetty 1985 - Indentation fracture of WC-Co cermets, see references above), and was 9.5MPa*m 1 / 2 The thermal conductivity (TC) was 29 W / m*K (measured at 40°C by the laser flash method).
[0043] Table 1 shows the properties determined by comparison with a cemented carbide having a similar composition but without the addition of cubic metal carbides and a similar binder metal content.
[0044] Example 2 As the starting powder, BET WC powder with a value of 90 nm, d BET Cobalt metal powder with a value of 205 nm, d BET TiC powder with a value of 610 nm, d BET TaC powder with a value of 370 nm, d BET Cr3C2 powder with a value of 430 nm, and d BETVC powder with a value of 350 nm was used. 200 g of a mixture of 68.9 vol.% (80.6 wt.%) WC, 16 vol.% (10.6 wt.%) Co, 4 vol.% (2.6 wt.%) TiC, 7 vol.% (4.3 wt.%) TaC, 1.9 vol.% (0.9 wt.%) Cr3C2 and 2.2 vol.% (1 wt.%) VC was ground in n-heptane in a ball mill for 48 h. The resulting dispersion of cemented carbide was dried and uniaxially pressed at a pressure of 300 MPa to obtain rectangular specimens whose green density was more than 50% of the density expected for the solid (theoretical density). The specimens were compressed under vacuum at a temperature of 1450 °C with a holding time of 30 min to more than 95% of the theoretical density, followed by a final compression at the same temperature under argon atmosphere (Sinter-HIP technique). The specimens proved to be fully dense under an optical microscope. The porosity according to ISO 4505 corresponds to A02, B00, C00. The Vickers hardness is 1690HV10, and the fracture toughness (K 1C ) was calculated by measuring the crack length and using Shetty's formula (Shetty 1985 - Indentation fracture of WC-Co cermets, see references above), and was found to be 9.7MPa*m 1 / 2 The thermal conductivity (TC) was 39 W / m*K (measured at 40°C by the laser flash method).
[0045] Table 1 shows the properties obtained by comparison with the properties of Example 1.
[0046] Table 1: Composition and achieved hardness, fracture toughness, and thermal conductivity of nanoscale or ultrafine cemented carbides with binder metal content of 16 ± 0.2 vol.% and cubic metal carbide (MeC) additions of 17 vol.% and 11 vol.%, respectively. [Table 1]
[0047] Example 3 As the starting powder, BET WC powder with a value of 90 nm, d BET Cobalt metal powder with a value of 205 nm, d BETTiC powder with a value of 610 nm, d BET TaC powder with a value of 370 nm, d BET Cr3C2 powder with a value of 430 nm, d BET VC powder with a value of 350 nm was used. 200 g of a mixture of 68.5 vol.% (79.1 wt.%) WC, 10 vol.% (6.5 wt.%) Co, 10.1 vol.% (3.7 wt.%) TiC, 9 vol.% (9.6 wt.%) TaC, 1.2 vol.% (0.6 wt.%) Cr3C2, and 1.2 vol.% (0.5 wt.%) VC were ball milled in n-heptane for 44 h. The resulting dispersion of cemented carbide was dried and uniaxially pressed at a pressure of 300 MPa to obtain rectangular specimens whose green density was more than 50% of the density expected for the solid (theoretical density). The specimens were compressed under vacuum at a temperature of 1460 °C with a holding time of 30 min to more than 95% of the theoretical density, followed by a final compression at the same temperature under argon atmosphere (Sinter-HIP technique). The specimens proved to be fully dense under an optical microscope. The porosity according to ISO 4505 corresponds to A02, B00, C00. The Vickers hardness is 2020HV10, and the fracture toughness (K 1C ) was calculated by measuring the crack length and using Shetty's formula (Shetty 1985 - Indentation fracture of WC-Co cermets, see references above), and was found to be 8.5MPa*m 1 / 2 The thermal conductivity (TC) was 35 W / m*K (measured at 40°C by the laser flash method).
[0048] Table 2 shows the properties determined by comparison with a cemented carbide having a similar composition but without the addition of cubic metal carbides and a binder metal content.
[0049] Table 2: Composition of nanoscale or ultrafine cemented carbides with binder metal content of 10 ± 0.2 vol.% with and without the addition of cubic metal carbide (MeC) and the achieved hardness, fracture toughness and thermal conductivity. [Table 2]
[0050] As can be seen from Tables 1 and 2, the cemented carbide of the present invention according to the examples has improved fracture toughness over conventional cemented carbide and has lower thermal conductivity without adversely affecting the Vickers hardness of the cemented carbide according to the present invention within the acceptable tolerance range of ±20HV10.
[0051] FIG. 1 is a scanning electron micrograph of a cemented carbide according to the invention, showing a regularly repeating distribution of additional metal carbide phases with an average spacing of about 1-3 μm. The photograph was taken with an electron microscope equipped with an EsB detector at an acceleration voltage of 2 kV and a magnification of 10,000 times. The numbers represent: 1 - tungsten carbide phase, 2 - cubic metal carbide phase, 2 - binder metal phase.
Claims
1. A cemented carbide, a) a tungsten carbide phase having an average grain size of 0.05 to 0.5 μm, or 0.05 to 0.23 μm, or 0.05 to 0.09 μm; b) additional metal carbide phases; c) a binder metal phase; the additional metal carbide phase is present in a cubic crystal structure at room temperature, the proportion of the additional metal carbide phase in the cemented carbide is at least 4% by volume, based on the total volume of the cemented carbide, and the average grain size is determined by the linear intercept method according to ISO 4499-2, The cemented carbide has a thermal conductivity of less than 50 W / m*K at 40°C as measured by a laser flash method; 1. A cemented carbide, wherein the proportion of the tungsten carbide in the cemented carbide is 40-95 volume % and the proportion of the additional metal carbide phase in the cemented carbide is 4-20 volume %, based on the total volume of the cemented carbide.
2. 2. The cemented carbide of claim 1, characterized in that the additional metal carbide phase is selected from the group consisting of titanium carbide (TiC), tantalum carbide (TaC), niobium carbide (NbC), hafnium carbide (HfC), zirconium carbide, mixtures thereof, and mixed carbides of these compounds.
3. 3. A cemented carbide according to claim 1 or 2, characterized in that the additional metal carbide phase has an average grain size, determined by the linear intercept method according to ISO 4499-2, of 0.3 to 4 μm, or 0.5 to 1.5 μm.
4. 4. The cemented carbide according to claim 1, characterized in that the additional metal carbide phases are present in the cemented carbide in a regularly repeating distribution with an average spacing of 0.5 to 10 μm, or 1 to 3 μm, determined by linear analysis of electron micrographs of sections (linear intercept method).
5. A cemented carbide according to any one of claims 1 to 4, characterized in that the binder metal phase is selected from the group consisting of iron, cobalt, nickel and mixtures thereof.
6. 6. The cemented carbide of claim 5, wherein the binder metal phase is a mixture of iron, cobalt and nickel, each of which is present in an amount of at least 1% by weight.
7. 7. The cemented carbide of claim 1, further comprising a grain growth inhibitor selected from the group consisting of vanadium carbide, chromium carbide, mixtures thereof, and mixed carbides of these compounds.
8. The cemented carbide according to any one of claims 1 to 7, characterized in that the tungsten carbide phase in the cemented carbide is composed of 40 to 90 volume % based on the total volume of the cemented carbide.
9. i) a) Average particle size d of 0.05 to 0.3 μm BET tungsten carbide powder having b) exists in a cubic crystal structure at room temperature (25° C.) and has an average particle size d BET an additional metal carbide powder having an average particle size of 0.3 to 5 μm or 0.4 to 1 μm; and c) a binder metal powder; and ii) forming and sintering the mixture; A process for preparing the cemented carbide according to any one of claims 1 to 8, comprising:
10. The average particle size d of the tungsten carbide powder BET The process of claim 9, wherein the thickness is 0.05 to 0.25 μm, or 0.05 to 0.2 μm.
11. The process according to claim 9, characterized in that the sintering is carried out at a temperature between 1150 and 1550°C.
12. Use of a hardmetal according to any one of claims 1 to 8 for the manufacture of tools.
13. A part obtained by molding the cemented carbide according to any one of claims 1 to 8.
14. 14. The part of claim 13, wherein the part is a drill, a solid carbide cutter, an indexable tip, a saw blade, a forming die, a seal ring, an extrusion punch, a press die, and a wear part.
Citation Information
Patent Citations
Hard alloy
CN103540823A
WC base cemented carbide and its production
JP1998237650A
CEMENTED CERAMIC TOOLS MADE FROM ULTRA-FINE SOLID SOLUTION POWDER, MANUFACTURING METHOD THEREOF, AND MATERIALS THEREOF
JP1998512624A
Hard metal with low thermal conductivity
JP2003507578A
Cemented carbide, its production method, and cutting tool using the same
JP2004190118A